The future of flourishing in veterinary medicine: a systems-informed positive psychology approach in veterinary education - Corrigan, Virginia K.; Newman, Rebecca L.; Richmond, Philip; Strand, Elizabeth B.; Vaisman, Josh M. (Frontiers in Veterinary Science, 2025)
Individuals in the veterinary profession are experiencing significant mental health and wellbeing challenges. A holistic view of wellbeing, which encompasses both physical and mental health, underscores their interconnected nature. This integrated approach reduces the artificial separation of wellbeing facets, and highlights how mental states influence not only individuals, but also their interactions with animals, the environment, and others in the workplace. Wellbeing challenges in veterinary medicine may contribute to negative impacts in animal, human, and environmental health. Veterinary education institutions and systems are also experiencing complex challenges as they adapt to rapidly changing societal, workforce, and professional wellbeing related pressures. This review paper explores the field of positive psychology and its application in educational contexts, commonly known as positive education. A thorough exploration of the systems-informed positive education approach and ways in which it can proactively enhance veterinary professional wellbeing from within the veterinary education ecosystem are presented. It is important to recognize that individual self-care, while valuable, cannot compensate for systemic dysfunctions such as poor team dynamics, ineffective leadership, or organizational culture issues. Addressing these systemic factors is critical for creating environments that support sustained flourishing. Positive psychology interventions delivered through the pathways of individuals, groups, and organizations specifically within a veterinary education context are discussed. Limitations, considerations, and proposed measurement strategies are reviewed. The implications of implementing a systems-informed positive psychology approach to enhance wellbeing in veterinary education include creating curriculum and cultures that enable flourishing within veterinary education institutions. Strengthening the individual and collective wellbeing of veterinary professionals has the potential to enhance the quality of care provided to animals, which has myriad positive implications for animal caregivers, their communities, the environment, and society.